Hyaluronic acid microparticles loaded with Shuang-Huang-Lian phospholipid complex for sustained pulmonary delivery: An in vitro and in vivo evaluation - Weiya Chen; Jiaxing Wei; Chenyang Yu; Xiang Fu; Yuzhuo Li; Yonghong Liao (Science of Traditional Chinese Medicine)
Abstract. Background. Inhalation-based combination therapy has gained increasing attention for local treatments. However, a key challenge remains in ensuring the sustained pulmonary release of multiple active ingredients, particularly in traditional Chinese medicine (TCM) formulations. Objective. This study investigates a novel PulmoSphere-based inhalable carrier designed for the sustained pulmonary release of multiple active ingredients, using Shuang-Huang-Lian as a model TCM formulation containing three chemical markers. Materials and methods. The carrier was developed using PulmoSphere technology, incorporating phospholipid complexes of the chemical markers and hyaluronic acid (HA) into spray-dried microparticles. The aerodynamic properties, release characteristics, pulmonary distribution, and anti-inflammatory efficacy of different formulations were evaluated in vitro and in mice. Results. The microparticles retained the excellent aerodynamic properties of conventional PulmoSphere particles, with a mass median aerodynamic diameter of approximately 3.1 μm and a fine particle fraction of approximately 55%. Compared to free Shuang-Huang-Lian or phospholipid complex-loaded PulmoSphere particles, the HA-containing particles prolonged the retention of chemical markers in the lung epithelial lining fluid, demonstrating sustained release in vivo. Additionally, the HA-containing formulation enhanced the exposure of the three chemical markers to immune cells and lung tissues, leading to improved and prolonged anti-inflammatory effects, even at decreased doses. Conclusion. This novel inhalable particle system represents a promising approach for sustained pulmonary co-delivery of multiple active ingredients, offering enhanced and extended local therapeutic efficacy.